2009
DOI: 10.1177/0017896909345195
|View full text |Cite
|
Sign up to set email alerts
|

Tanning behaviour among young frequent tanners is related to attitudes and not lack of knowledge about the dangers

Abstract: Objective To examine the importance of tanning among students in relation to attitudes and knowledge regarding skin cancer prevention. Design A cross-sectional survey. Setting College students at a major Midwestern university Methods Students were recruited to complete a self-administered questionnaire that included information on sun-sensitivity, knowledge and tanning attitudes and behaviors. Survey sampling statistical techniques that account for clustering among the 163 students recruited were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 17 publications
6
67
0
Order By: Relevance
“…This is widely reported in western literature among all ages of avid tanners,19 44–47 but this study demonstrates its presence also in those without a preference for tanning. Paradoxically, health risks associated with usage of low factor sun protection were known, but taken as informed ones to enable tanning, while sunbeds were avoided.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…This is widely reported in western literature among all ages of avid tanners,19 44–47 but this study demonstrates its presence also in those without a preference for tanning. Paradoxically, health risks associated with usage of low factor sun protection were known, but taken as informed ones to enable tanning, while sunbeds were avoided.…”
Section: Discussionsupporting
confidence: 64%
“…12 16 19 34 Degree-related UVR knowledge, particularly those studying medicine, also appeared of little influence; similarly found among Swedish university students 35. While all participants acknowledged the importance of sun protection, primarily sunscreen, this was frequently limited to being abroad, causing complacency in England.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Social tanning has been identified as a source of tanning motive because of friends' perceptions; as a result, individuals may feel that a tan is important in making one attractive (Dennis, Lowe, & Snetselaar, 2009). Previous research on indoor-tanning behaviors has revealed that parents' use of tanning devices is a significant predictor of children's tanning device usage (Cokkinides & Weinstock, 2003).…”
mentioning
confidence: 99%